KEKUATAN SURAT ELEKTRONIK SEBAGAI ALAT BUKTI DALAM PERSIDANGAN DITINJAU DARI HUKUM ACARA PIDANA - Yudhistira, Yudhistira; Sekar, I Dewa Nyoman; Sudjana, I Ketut (Kertha Wicara : Journal Ilmu Hukum; Vol 1 No 01 (2012))
The function of proof in law of criminal procedure is to find the truth and reinforces the conviction of judges to mistakes charged the defendant.In article 184 paragraph (1) Indonesian law of criminal procedure, legal means of evidence shall be : the testimony of a witness, the testimony of an expert, a document, an indication, the testimony of the accused. Age of increasingly sophisticated led to the rise of cyber crime and in the process proving cybercrime requires electronic evidence, for example electronic mail.
Keywords: Proof, law of criminal procedure, evidence, electronic mail